Implementasi Internet Provider Dengan Metode Intrusion Detection System Dan Simplewall Untuk Mencegah Serangan Ddos - Hafizh Kurnia; Riswal Hanafi Siregar (CV. Multi Kreasi Media, 2023)
Distributed Denial of Services (DDOS) is one type of exploitation of weaknesses on a web. DDOS is an attack attempt against a server on the internet network by flooding a lot of data on the network traffic to disrupt normal traffic on the server. Intrusion Detection System (IDS) is a system that can detect suspicious activity in a system or network. Simplewall is computer software that is used as a firewall to provide total protection against any unwanted access. Intrusion Detection Systems (IDS) and Simplewall as a deterrent to intruders on computer network servers and even DDOS attacks at once.